1998
DOI: 10.1007/s001980050068
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Bone Mineral Assessment at the Forearm: A Review

Abstract: Bone mineral density and geometric properties of the human forearm can be measured to determine the amount of bone or bone loss at the scanning site and to predict the risk of forearm fractures. These forearm measurements are also used to estimate bone mass at remote anatomical locations and thereby estimate the risk for spine, hip and other fractures. The peripheral location of the human forearm, with its relatively small amount of surrounding soft tissue, improves the accuracy and the precision of bone mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 120 publications
3
49
1
3
Order By: Relevance
“…The percent coefficient of variation of TBD with the LD-100 system was also similar to that with pQCT reported in the literature [4,25]. The measurement sites adopted by the LD-100 and pQCT systems were slightly different, although on the same radius of the subjects.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The percent coefficient of variation of TBD with the LD-100 system was also similar to that with pQCT reported in the literature [4,25]. The measurement sites adopted by the LD-100 and pQCT systems were slightly different, although on the same radius of the subjects.…”
Section: Discussionsupporting
confidence: 66%
“…As mentioned in Materials and methods, the measurement site for the LD-100 system (the nearest point to the distal 5.5% point of the radius for both TBD and CoTh) was chosen to select a perpendicular incidence site for the ultrasonic beam and to avoid interference waves overlapping with the transmitted signal. On the other hand, the measurement site used for the pQCT system is well accepted as 4% of the forearm length proximal to the distal end of the radius for TBD and the mid-radial 20% site for CoTh, adopting the area of high mineral content and trabecular bone percentage for the former and the area with a relatively round shape of the cross-section of the radius, permitting the application of the circular ring model, for the latter [25,[27][28][29][30][31]. In the present study, a highly significant correlation was found between the LD-100 and pQCT measurement values in TBD and CoTh, suggesting that evaluation of the bone status, at least the bone status of the forearm, can be similarly evaluated at positions used by both systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…b Showing the trabecular BMD difference between section 1 and section 2 at baseline (mg/cm 3 ). c Showing the total BMD difference between section 1 and section 2 at baseline (mg/cm 3 ) large, up to 40 mm 2 over the very small distance of 1.2 mm. The magnitude of decrease in CSA between the distal end and diaphysis of the radius has been measured in cadaver studies [4] and in small clinical studies of adolescents and adults [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…There are three common sites of measurement for pQCT at the radius [3]: the 4% distal site and the 50% or 66% midshaft site. In adults, measurements of cross-sectional area (CSA), bone mineral content (BMC) and volumetric BMD (BMD) at the distal forearm are made at 4% of the forearm length, proximal to the distal medial articular surface of the radius.…”
Section: Introductionmentioning
confidence: 99%